Diagnostic study of FMD virus in different area in Iraq: Ameen Ahmad Sabar1 , Anton S. Al-Banna1 , Laith MS. Abdul-Rasoul2 and Barraq K.Abood2 - Sabar, Ameen Ahmad (The Iraqi Journal of Veterinary Medicine, 2012)
Seventy four (74) samples from cattle, buffalo, goat and sheep were tested to isolatethe FMD virus, 23 isolates of the virus showed Cytopathic Effect (CPE) on the different typesof cell culture. The CPE appears after 24 hours on fetal lamb kidney (FLK) cells, 48 hours on the fetalbovine kidney (FBK), 30 hours on primary Fetal Bovine Thyroid cell (BTY) and 20 hours onthe primary fetal ovine thyroid cells (OTY). Solid phase ELISA test showed three serotypesof FMD virus O, A and Asia1. One step real time RT-PCR for the diagnosis of FMDV byusing 5UTR FMDV primers and taqman probe (SA-IR-219-246F, SA-IR-315-293R andSAmulti2-P-IR-292-269R). Samples were tested, showed 23 positive machines by using theApplied Biosystem Fast 7500 real time PCR.